1996
DOI: 10.1152/jn.1996.76.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Backward and forward walking use different patterns of phase-dependent modulation of cutaneous reflexes in humans

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.Journal o r N eu ro ph y sio lo g y Vol. 76, No. I. July 1996. Printed in U.S.A. 1 . The phase-dependent modulation of medium-latency (P2) (70-80 ms) responses in semitendinosus (ST), biceps femoris (BF), rectus femoris (RF), and tibialis anterior (TA) was studied with the use of low-intensity stimulation (2 times perception threshold) of the sural nerve. The shocks were given in a random order at 16 phases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 27 publications
12
95
0
1
Order By: Relevance
“…This finding adds to previous evidence of phase-dependent effects of flexion reflex stimuli during forward and backward walking rhythms, especially from studies of cats and humans (Forssberg et al, 1975(Forssberg et al, , 1977Andersson et al, 1978;Schomburg et al, 1978;Forssberg, 1979;Wand et al, 1980;Crenna and Frigo, 1984;Buford and Smith, 1990;Duysens et al, 1990;Duysens et al, 1992;Duysens et al, 1996;Degtyarenko et al, 1998;Burke, 1999;Ménard et al, 1999;Perreault et al, 1999;McCrea, 2001;Spaich et al, 2004;Quevedo et al, 2005;Sandrini et al, 2005;Hultborn, 2006;Knikou et al, 2006;Knikou, 2007;Knikou et al, 2009;Duysens et al, 2013) and during swimming (Lennard, 1985) and all three forms of scratching rhythms in turtles (Currie and Stein, 1989). Collectively, these findings suggest that leg flexion reflex (as well as other leg reflexes) are modulated or gated according to hip phase for multiple forms of locomotion and scratching in limbed vertebrates generally.…”
Section: Discussionsupporting
confidence: 83%
“…This finding adds to previous evidence of phase-dependent effects of flexion reflex stimuli during forward and backward walking rhythms, especially from studies of cats and humans (Forssberg et al, 1975(Forssberg et al, , 1977Andersson et al, 1978;Schomburg et al, 1978;Forssberg, 1979;Wand et al, 1980;Crenna and Frigo, 1984;Buford and Smith, 1990;Duysens et al, 1990;Duysens et al, 1992;Duysens et al, 1996;Degtyarenko et al, 1998;Burke, 1999;Ménard et al, 1999;Perreault et al, 1999;McCrea, 2001;Spaich et al, 2004;Quevedo et al, 2005;Sandrini et al, 2005;Hultborn, 2006;Knikou et al, 2006;Knikou, 2007;Knikou et al, 2009;Duysens et al, 2013) and during swimming (Lennard, 1985) and all three forms of scratching rhythms in turtles (Currie and Stein, 1989). Collectively, these findings suggest that leg flexion reflex (as well as other leg reflexes) are modulated or gated according to hip phase for multiple forms of locomotion and scratching in limbed vertebrates generally.…”
Section: Discussionsupporting
confidence: 83%
“…The present results show that the amplitude o f the BF tendon jerk reflex is at a maximum near the end of the swing phase, in a period when this muscle is normally very active both during 'reduced' (this study) and normal walk ing [5]. This finding lends support to the hypothesis that activation of this muscle at end swing is at least partly generated through stretch reflexes [7].…”
Section: H Waa Van De Crommert Et a L / Brainsupporting
confidence: 85%
“…Furthermore, the data illustrate that during this critical period, just prior to foot placement, there is a highly differentiated control of : and reflex pathways. In contrast to cutaneous reflexes in BF which are suppressed in this phase during walking [5], sensibility to cutaneous stimuli are at a maxi mum (subjective judgments of intensity; [4]). Similarly, the BF stretch reflexes are then largest.…”
Section: H Waa Van De Crommert Et a L / Brainmentioning
confidence: 86%
See 1 more Smart Citation
“…Winter et al (1989) suggested that " backward walking is almost a simple reversal of forward walking" [95]. Duysens et al (1996) studied the regulation of the gain of cutaneous reflex pathways during BW [96], The hypothesis was that if BW walking in humans is pro duced by a forward motor program, reversed in se quence, then the phase-dependent modulation pattern of cutaneous reflexes should be reversed in sequence during BW. At one of the 16 different phases of the step cycle an electrical stimulus train was applied over the sural nerve at two perception threshold (PT) both during FW and BW and unpredictable for the subject.…”
Section: 17 Backward Walkingmentioning
confidence: 99%